PROJEK NGGIWAR : STUDI PADA RUANG KREATIVITAS DAN KEMANDIRIAN DI SD EKSPERIMENTAL MANGUNAN YOGYAKARTA - Setyaningsih, Clara Dwi; Vendira Putri , Verena Agna; Chandra Dewi, Laura Savina; Prasetya, Andreas Erwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to explore the uniqueness of the Nggiwar Project implemented at SD Eksperimental Mangunan, Yogyakarta. This research employed a descriptive qualitative approach and was conducted at SD Eksperimental Mangunan from February to May 2025. Data were collected through participant observation, in-depth interviews, and documentation. The subjects of this study included class facilitators and second-grade students of SD Eksperimental Mangunan, while the object of the research was the analysis of the unique characteristics of the Nggiwar Project. To ensure data validity, triangulation techniques were applied. Data analysis followed the qualitative method stages proposed by Sugiyono (2019), which include data reduction, data display, and conclusion drawing. The results indicate that the learning process at SD Eksperimental Mangunan emphasizes freedom, creativity, and active student involvement in knowledge exploration. This is clearly reflected in the implementation of the Nggiwar Project, a distinctive instructional method at the school. The Nggiwar Project serves as a concrete manifestation of the school's effort to shape students who are explorative, collaborative, and integrative thinkers, in alignment with the school’s educational vision.